Exergames as a tool for the acquisition and development of motor skills and abilities: A systematic review - Capistrano R.* (2017)
© 2017 Sociedade de Pediatria de São Paulo.Objective: To analyze the literature on the effectiveness of exergames in physical education classes and in the acquisition and development of motor skills and abilities. Data source: The analyses were carried out by two independent evaluators, limited to English and Portuguese, in four databases: Web of Science, Science Direct, Scopus and PubMed, without restrictions related with year. The keywords used were: "Exergames and motor learning and motor skill" and "Exergames and motor skill and physical education". The inclusion criteria were: articles that evaluated the effectiveness of exergames in physical education classes regarding the acquisition and development of motor skills. The following were excluded: books, theses and dissertations; repetitions; articles published in proceedings and conference summaries; and studies with sick children and/or use of the tool for rehabilitation purposes. Data synthesis: 96 publications were found, and 8 studies were selected for a final review. The quality of the articles was evaluated using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) scale and the Physiotherapy Evidence Database (PEDro) scale. Evidence was found on the recurring positive effects of exergames in both motor skills acquisition and motor skills development. Conclusions: Exergames, when used in a conscious manner - so as to not completely replace sports and other recreational activities -, incorporate good strategies for parents and physical education teachers in motivating children and adolescents to practice physical exercise.